Understanding female nurses' decision-making to participate in continuing professional development activities: a grounded theory study in a Saudi context - Alanazi, Aminah (2024)
Background: Continuing professional development (CPD) offers nurses the opportunity to broaden their knowledge and skills, as well as developing their competencies and abilities to practice in a way that is not generally available during basic education or daily work. Expanded nursing knowledge and practice together with rapid changes in healthcare and the explosion of technology have created an ever-greater need for appropriate CPD opportunities. Many studies have explored the various factors, motivations and barriers that can influence nurses’ ability to participate in CPD activities. However, in the context of the Kingdom of Saudi Arabia (KSA), where the nursing profession faces many unique challenges, it is possible that cultural and other contextual factors could uncover different factors and dimensions that influence nurses' CPD.